Diagnostic performances of 68Ga-DOTATOC versus 18Fluorodeoxyglucose positron emission tomography in pulmonary carcinoid tumours and interrelationship with histological features. (7th February 2019) - Lococo, Filippo; Rapicetta, Cristian; Mengoli, Maria Cecilia; Filice, Angelina; Paci, Massimiliano; Di Stefano, Teresa; Coruzzi, Chiara; Versari, Annibale
Abstract: Few data are available about radio-receptorial positron emission tomography (PET) results by the use of 68 Ga-DOTA-peptides in pulmonary carcinoid tumours. In this study, we retrospectively analysed 68 Ga-DOTATOC/PET and 18 Fluorodeoxyglucose (FDG) PET diagnostic performances in 62 pulmonary carcinoids (occurring in 57 patients) and interrelationship with histological features. All patients underwent at least 1 PET/computed tomography: 26 patients received 68 Ga-DOTATOC, 52 patients had 18 F-FDG and 20 patients received both techniques. There were 55 typical carcinoids and 7 atypical carcinoids. 68 Ga-DOTATOC/PET recorded an 88.4% overall detection rate (DR) (meanSUVmax : 15.5); 18 F-FDG/PET a DR of 53.8% (meanSUVmax : 3.2). When adopted a maximum standardized uptake value-threshold of 1.5, DRs of 68 Ga-DOTATOC and 18 F-FDG/PET increased to 100% and 80.8%, respectively. Moreover, DRs in both techniques vary considerably according to histology with 68 Ga-DOTATOC/PET having better performances in typical carcinoids than in atypical carcinoids (DR: 91.7% vs 50.0%, P  = 0.076). We also observed a significant correlation between a low number of mitoses (<2/10 high-power field) and 68 Ga-DOTATOC/PET-positivity ( P  = 0.004), and an association trend ( P  = 0.076) between necrosis and 68 Ga-DOTATOC/PET-negativity. In conclusion, 68 Ga-DOTATOC had better diagnostic performances than 18 F-FDG/PET in detecting pulmonary carcinoids. DRs of both techniques remarkably varied according to histology with 68 Ga-DOTATOC/PET performing at its best in typical carcinoids, whereas 18 F-FDG/PET did the same in atypical carcinoids. 68 Ga-DOTATOC/PET results were presumably associated with the number of mitoses and the presence of necrosis.